Interfacial assessment of cention forte vs. equia forte and two forms of calcium silicate cements at two time intervals - Heba Abdelkafy; Nada A. Salem; Rasha Mohamed Marzouk; Alaa M. Eldehna (Nature Publishing Group, 2024)
Abstract Aim Assessment of interfacial gaps and mechanical impact of the materials layering between Cention Forte and Equia Forte restorations with two forms of Calcium Silicate Cements (CSCs) at the interfacial surface at two-time intervals. Methodology Six groups of 72 primary molars were categorized by restorative material type and CSCs: Cention Forte(C), Cention Forte without primer (Cx), and Equia Forte (EQ). All were applied over MTA Angelus powder (M) or Bio-C Repair putty (P). Restorative materials were applied immediately (subgroup A) or delayed (Subgroup B). SEM was used to detect interface gaps. EDX measured element migration from the interface at specific distances. Vickers Microhardness Tester assessed microhardness. Results Regarding SEM, there were no gaps between CSCs interfaces of both types (Powder and Putty) with all restorations at two-time intervals. Microhardness, there was a statistically nonsignificant difference between subgroups A & B in all groups except at 200 µm in the Cention groups (subgroup A) was significantly lower than (subgroup B) (P = 0.002, 0.03) respectively. At 400 µm in the MTA Angelus powder Group Cx, subgroup A was significantly higher than subgroup B (P = 0.003*). While Bio-C Repair putty in Group EQ (subgroup A) was significantly higher than (Subgroup B) (P < 0.0001*). Conclusions The delayed application of Cention Forte over two types of CSCs is useful in getting the maximum HV and, in turn, the long survival rate of the filling. Immediate application of Cention Forte without primer is better over both types of CSCs. The delayed application of Equia Forte over MTA angelus powder is more considerable.